Analysis of the Use of Electronic Medical Records Regarding Law Number 17 of 2023 in Indonesia - Br.Sembiring, Tamaulina; Meutia, Cut Yeni (Formosa Journal of Science and Technology, 2024)
Health services are the most important public service after food in every country. Although ideally, the state should fully manage health services to ensure equal access for all citizens, in reality not all health services can be managed by the state due to limited resources. As the global situation progresses, the health crisis threatens millions of lives, and many countries face a lack of quality and adequate health services. Key barriers include a lack of health infrastructure, insufficient professional staff, poor public health implementation, and limited access to health information. Information technology has become an important solution to overcome this problem, with Electronic Medical Records (RME) as one of the key innovations. RME records patient health history electronically, which helps improve the quality of healthcare services through better information management. The implementation of RME in Indonesia is regulated by Law Number 17 of 2023 concerning Health, which requires health service facilities to maintain electronic medical records. However, challenges such as limited infrastructure, lack of skilled professionals, and issues of confidentiality and security of patient data need to be overcome. For this reason, it is necessary to improve information technology infrastructure, training for medical personnel, financial support, strict data security policies, as well as collaboration between the government, health facilities and technology providers.